2021
DOI: 10.3389/fbioe.2021.659989
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis-Related Degeneration Alters the Biomechanical Properties of Human Menisci Before the Articular Cartilage

Abstract: An exact understanding of the interplay between the articulating tissues of the knee joint in relation to the osteoarthritis (OA)-related degeneration process is of considerable interest. Therefore, the aim of the present study was to characterize the biomechanical properties of mildly and severely degenerated human knee joints, including their menisci and tibial and femoral articular cartilage (AC) surfaces. A spatial biomechanical mapping of the articulating knee joint surfaces of 12 mildly and 12 severely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 84 publications
(137 reference statements)
2
28
0
Order By: Relevance
“…Normal menisci have a highly anisotropic structure that is mainly composed of water (75%), collagen (23%), water-binding glycosaminoglycans (1%), and other matrix components leading to a time-dependent viscoelastic behavior ( Herwig et al, 1984 ; Pereira et al, 2014 ; Seitz et al, 2021 ). While under static equilibrium conditions ( Tibesku et al, 2004 ; Martin Seitz et al, 2013 ; Schwer et al, 2020 ) and repetitive loading ( Kessler et al, 2006 ), the menisci exhibit considerable axial deformation, high impact, or shock loads, as seen, e.g., during jump landings, leading to an increase in their stiffness, and thus, to a decrease in the ability to reduce the transmitted stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Normal menisci have a highly anisotropic structure that is mainly composed of water (75%), collagen (23%), water-binding glycosaminoglycans (1%), and other matrix components leading to a time-dependent viscoelastic behavior ( Herwig et al, 1984 ; Pereira et al, 2014 ; Seitz et al, 2021 ). While under static equilibrium conditions ( Tibesku et al, 2004 ; Martin Seitz et al, 2013 ; Schwer et al, 2020 ) and repetitive loading ( Kessler et al, 2006 ), the menisci exhibit considerable axial deformation, high impact, or shock loads, as seen, e.g., during jump landings, leading to an increase in their stiffness, and thus, to a decrease in the ability to reduce the transmitted stresses.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of age, degenerative injury appears inside meniscus which is mainly manifested by the change of its internal structures, and horizontal tear is the main type of injury on MRI images [2]. Degenerative lesion of menisci is considered of the early stage of the knee osteoarthritis [3,4]. And literature statistics showed that 90% of symptomatic osteoarthritis patients' had positive meniscus lesions on their MRI pictures [5] and osteoarthritis-related medial gonarthrosis is much more frequent than the lateral [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have identified a relationship between meniscal degeneration and the progression of KOA. Seitz et al (2021) recently demonstrated that the biomechanical alterations and degeneration associated with KOA were first detectable in menisci and occurred before degeneration of the articular cartilage. Together, these findings suggest that the mechanobiology of the meniscus plays a key role in the pathogenesis of KOA.…”
Section: Introductionmentioning
confidence: 99%
“…If this mechanism were to be identified, this information could lead to a breakthrough discovery that would have important implications for meniscus research including studies on knee osteoarthritis (KOA). KOA is a degenerative disease of the knee joint that poses a huge annual socioeconomic burden (Seitz et al, 2021) and is characterized by progressive pain, joint immobility, and a reduced quality of life (Thomas et al, 2017). It is well established that biomechanical dysfunctions of the knee joint are contributing factors to the initiation and progression of the disease (Egloff et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation